2008
DOI: 10.1007/s11606-008-0726-6
|View full text |Cite
|
Sign up to set email alerts
|

Content of Weblogs Written by Health Professionals

Abstract: BACKGROUND: Medical weblogs ("blogs") have emerged as a new connection between health professionals and the public. OBJECTIVE:To examine the scope and content of medical blogs and approximate how often blog authors commented about patients, violated patient privacy, or displayed a lack of professionalism. DESIGN:We defined medical blogs as those that contain some medical content and were apparently written by physicians or nurses. We used the Google search term "medical blog" to begin a modified snowball sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
127
1
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(134 citation statements)
references
References 12 publications
(8 reference statements)
0
127
1
6
Order By: Relevance
“…3 This violation was also observed by Lagu et al; however, the posts were carried out by people who identified themselves as medics or nurses. 6 In our study, more than 90 % of participants considered inappropriate posts that involve violation of patients' privacy. However, we observed that a significant proportion of participants did not recognize the publication in social media of photos of medical students playing with hospitalized children or holding newborns in the neonatal unit as a violation of patients' privacy.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…3 This violation was also observed by Lagu et al; however, the posts were carried out by people who identified themselves as medics or nurses. 6 In our study, more than 90 % of participants considered inappropriate posts that involve violation of patients' privacy. However, we observed that a significant proportion of participants did not recognize the publication in social media of photos of medical students playing with hospitalized children or holding newborns in the neonatal unit as a violation of patients' privacy.…”
Section: Discussionmentioning
confidence: 79%
“…Other studies also have sought to quantify the occurrence of inappropriate online behaviors. [3][4][5][6] In the study by Chretien et al, for example, 60 % of American medical schools referred to incidents involving unprofessional postings by their students and 13 % of them corresponded to cases of violation of patients' privacy. 3 This violation was also observed by Lagu et al; however, the posts were carried out by people who identified themselves as medics or nurses.…”
Section: Discussionmentioning
confidence: 99%
“…For the most part, these have focused on the preponderance of easily searchable data on the Internet, 20 professionalism, 21 and the posting of potentially inappropriate material on various types of Web 2.0 formats, including YouTube, 22 weblogs, 23 and Twitter. 24 The structure of OSNs are such that they can dramatically blur the line between public and private spaces.…”
Section: Discussionmentioning
confidence: 99%
“…Firewalled in-house servers may afford additional security. Many public medical blogs are currently struggling with similar issues of privacy, anonymity, and reflection upon the profession 24 . This area warrants further exploration.…”
Section: Discussionmentioning
confidence: 99%